ANALISIS PENGGUNAAN GAMELAN EDUWEB PADA EKSTRAKURIKULER GAMELAN SISWA SEKOLAH DASAR - Nuzalfa, Siti Najla; Nurmeta, Irna Khaleda; Maula, Luthfi Hamdani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study analyzes the implementation of Gamelan Eduweb, an interactive digital learning platform, in extracurricular gamelan activities for elementary school students. The research aims to assess the effectiveness of this medium in enhancing students’ gamelan-playing skills. The study employs a descriptive qualitative method, involving elementary school students participating in extracurricular gamelan activities. Data were collected through interviews, observations, and documentation. The results indicate that Gamelan Eduweb significantly improves students’ abilities to play gamelan instruments both individually and in groups. This platform allows students to learn flexibly through features such as video tutorials, music notations, and gamelan history, which can be accessed anytime. Students showed enhanced skills in reading notation, understanding rhythms, and maintaining tempo during performances. However, the study also identified several challenges, including technical issues such as unstable internet connections and the lack of tutorials demonstrating complete instrument collaboration. These challenges were largely resolved through technical adjustments and teacher guidance. Additionally, learning with Gamelan Eduweb strengthened students’ understanding of cultural values, improved teamwork, and motivated them to appreciate Indonesia's traditional art heritage. In conclusion, Gamelan Eduweb is effective in supporting gamelan learning for elementary school students, offering additional benefits of accessibility and interactivity. This platform serves as a modern solution for preserving traditional arts while enriching students’ learning experiences in the context of arts education.